A computational approach for the seismic damage response under multiple earthquakes excitations of adjacent RC structures strengthened by ties. (December 2015) - Liolios, Angelos; Karabinis, Athanasios; Liolios, Asterios; Radev, Stefan; Georgiev, Krassimir; Georgiev, Ivan
Abstract: Civil Engineering systems of adjacent reinforced concrete (RC) structures, which have been environmentally degraded, are considered in order to be seismically strengthened by cable-elements (ties). A numerical approach for estimating the effects of pounding (seismic interaction) on the response of such adjacent structures under multiple earthquakes excitation is presented. For the system of the governing partial differential equations (PDE) a double discretization, in space by the Finite Element Method and in time by a direct incremental approach, is used. The unilateral behaviors of both, the cable-elements and the interfaces contact-constraints, are strictly taken into account and result to inequality constitutive conditions. So, in each time-step, a non-convex linear complementarity problem is solved. The decision for the optimal cable-strengthening scheme is obtained on the basis of computed damage indices. It is found that pounding and cable strengthening have significant effects on the earthquake response and, hence, on the seismic upgrading of existing adjacent RC structures.